Identifying Suitable Listeria innocua Strains as Surrogates for Listeria monocytogenes for Horticultural Products - Mohan, Vathsala; Wibisono, Reginald; de Hoop, Lana; Summers, Graeme; Fletcher, Graham C. (Frontiers in Microbiology, 2019)
A laboratory-based study testing 9 Listeria innocua strains independently and a cocktail of 11 Listeria monocytogenes strains was carried out. The aim was to identify suitable L. innocua strain(s) to model L. monocytogenes in inactivation experiments. Three separate inactivation procedures and a hurdle combination of the three were employed: thermal inactivation (55°C), UV-C irradiation (245 nm), and chemical sanitizer (TsunamiTM 100, a mixture of acetic acid, peroxyacetic acid, and hydrogen peroxide). The responses were strain dependent in the case of L. innocua with different strains responding differently to different regimes and L. innocua isolates generally responded differently to the L. monocytogenes cocktail. In the thermal inactivation treatment, inactivation of all strains including the L. monocytogenes cocktail plateaued after 120 min. In the case of chemical sanitizer, inactivation could be achieved at concentrations of 10 and 20 ppm with inactivation increasing with contact time up to 8 min, beyond which there was no significant benefit. All L. innocua strains except PFR16D08 were more sensitive than the L. monocytogenes cocktail to the hurdle treatment. PFR16D08 almost matched the resistance of the L. monocytogenes cocktail but was much more resistant to the individual treatments. A cocktail of two L. innocua strains (PFR 05A07 and PFR 05A10) had the closest responses to the hurdle treatment to those of the L. monocytogenes cocktail and is therefore recommended for hurdle experiments.